Evaluasi Penggunaan Aspirin Jangka Panjang terhadap Fungsi Ginjal Pasien Penyakit Jantung Koroner - Ema Pristi Yunita; Puji Astuti Nur Hidayanti; Cholid Tri Tjahjono (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Low-dose aspirin (75-100 mg/day) is a long-term platelet antiaggregation therapy for certain coronary heart disease (CHD) patients. This study aims to evaluate the long-term use of aspirin on kidney function by examining the changes in the levels of serum creatinine, blood urea nitrogen (BUN), and creatinine clearance of CHD patients. The research method used was a prospective observational cohort analysis. The number of study subjects was 37 CHD patients who took 80 mg/day of aspirin and never experienced kidney disease. Serum creatinine and BUN levels were examined in the 1st and 3rd month of the study. Patient creatinine clearance values were calculated using the Cockcroft-Gault equation. The results of the study showed that the mean levels of serum creatinine, BUN, and creatinine clearance on the 1st and 3rd month were 1.03 ± 0.27 mg/dL and 1.03 ± 0.29 mg/dL; 13.05 ± 4.10 mg/dL and 14.65 ± 4.44 mg/dL; 73.16 ± 18.14 mL/min and 72.92 ± 19.76 mL/min, respectively. The paired t-test results showed that the differences in the mean of creatinine serum, BUN, and creatinine clearance on the 1st and 3rd month were not statistically significant (p > 0.05). The One Way ANOVA test results on the effect of the duration of aspirin use on kidney function were also not statistically significant (p > 0.05) however there is a tendency to decrease creatinine clearance and increase in serum creatinine and BUN. Long-term use of low-dose aspirin has the potential to cause a decrease in kidney function that is seen from a decrease in creatinine clearance as well as an increase in serum creatinine and BUN.